PROFESSIONAL SOCIALIZATION OF NOVICE TEACHERS: BETWEEN THE CULTURE OF ACADEMIA AND THE WORKPLACE CULTURE - Kędzierska, Hanna Aldona (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
This paper discusses the outcomes of the first stage of conducted qualitative research on professional socialization of novice teachers. The presented analysis refers to the transition period from the role of a student to that of an employee and uncovers the less well-known empirically side of the coin in teacher training with regards to professional socialization of novice teachers – the perspective of constructing one’s professional path at the intersection of two cultures: the culture of academia and the workplace culture.